Diagnostic value of nuclear cardiology in coronary artery disease - Al Moudi, Mansour Z. (Curtin University, 2014)
This thesis investigates the diagnostic value of cardiac positron emission tomography when compared to single photon emission computed tomography for detection of coronary artery disease. This prospective study involves comparison of myocardial perfusion single photon emission computed tomography with coronary calcium scores; optimization of nuclear cardiac protocols in cardiac phantom experiments; and determination of diagnostic performance of cardiac positron emission tomography in the evaluation of myocardial viability in patients with significant coronary disease.